Comparison of Methods for Diagnosing Bacterial Vaginosis (Medical Forum Monthly, 2024)
Objective: To determine the laboratory method that best predicts Bacterial Vaginosis.Study Design: Descriptive Observational studyPlace and Duration of Study: This study was conducted in the Department of Microbiology, Sindh Medical College (DUHS) and Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from Jan. 2005 to Feb. 2007.Materials and Methods: A total of 150 randomly selected women were included in this study from OPD of various tertiary care hospitals and & family planning clinics of the city. In this study we compared and calculated the sensitivity, specificity and predictive value of positive and negative tests for wet mount, Gram stained vaginal smears and Gardnerella vaginalis (G.vaginalis) cultures with clinical sign Amsel’s criteria (Gold standard), for the diagnosis of bacterial vaginosis(B.V).Results: We diagnosed 54 (36%) cases of bacterial vaginosis by Gram’s staining method, 61 (41.7%) cases by Wet Mount method, and 42 (28.0%) cases by Amsel’s criteria and 47 (31.3%) cases by culturing.Conclusions: Amsel’s criteria were comparable with other laboratory tests for diagnosis of BV. Culture was laborious, expensive and least sensitive method.